Political Identity and Political Parties: Infrastructure Superstructure Nexus - Maskey, Prapanna (Patan Gyansagar, 2024)
The present research paper attempts to manifest the way to ensure economic growth and import substitution through political parties though the ultimate aim of political parties is to capture political power and keep control of the government. Paper identified the matrix of Vision, Man, Muscle and Money to win the election in national and local level. Economic production-oriented programs utilizing party member contributes political parties to achieve success. Thus, the production of goods and expansion of services grasping symbols can transform the economic condition and ensure solidarity of the party members. Marx rightly mentioned infrastructure determines the superstructure of the nation/state. Mishra (2007) consider aims of the CPNM is to ensure equal citizenship, equity, inclusion, social justice and progress. However, roadmap towards economic progressed is overlooked. Bhattachan (2003) presents political model to restructure political sphere of Nepal and regards the Panchayat political system as exclusionary political system. Realizing these aspect present paper attempts to show how intra economic prosperity and eventual sustainability is possible through concentration on symbolic political identity. Furthermore, research found charismatic leaders within every political party influence and motivate party members to contribute their time and attention in productive activities for the election symbols.